Queens and queenship - Woodacre, Elena (Past imperfect (ARC Humanities Press), 2021)
"This work looks at queenship in a global, timeless sense--examining the role of queens, empresses, and other royal women from the ancient and classical period through to nearly the present day on every continent. By looking at queenship in this comparative, longue durée way, we can start to see connecting threads and continuity over time and space as well as the change and development and comparisons of how the queen's role differed in various cultural contexts. A wide variety of examples are given to explain and contextualize key themes in queenship: family and dynasty, rulership, and image crafting. The introduction provides a brief overview of the development of queenship studies and a discussion of the ideals that queens were expected to conform to. This book offers a radically new perspective on queenship studies which enables new insights into the queen's role as the preeminent woman in the realm."--